2001
DOI: 10.1091/mbc.12.11.3515
|View full text |Cite
|
Sign up to set email alerts
|

Interactions among a Fimbrin, a Capping Protein, and an Actin-depolymerizing Factor in Organization of the Fission Yeast Actin Cytoskeleton

Abstract: We report studies of the fission yeast fimbrin-like protein Fim1, which contains two EF-hand domains and two actin-binding domains (ABD1 and ABD2). Fim1 is a component of both F-actin patches and the F-actin ring, but not of F-actin cables. Fim1 cross-links F-actin in vitro, but a Fim1 protein lacking either EF-hand domains (Fim1A12) or both the EF-hand domains and ABD1 (Fim1A2) has no actin cross-linking activity. Overexpression of Fim1 induced the formation of F-actin patches throughout the cell cortex, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
103
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(117 citation statements)
references
References 56 publications
(64 reference statements)
13
103
0
Order By: Relevance
“…Actin aggregates may function as an assembly center in the localization of integrin and other signaling molecules that are critical in the maturation of actin aggregates to functional sealing rings. L-plastin was described to be homologous with the F-actin-bundling protein fimbrin (59), and it is present in the podosomes of osteoclasts (2,60). However, its function in osteoclasts is highly unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Actin aggregates may function as an assembly center in the localization of integrin and other signaling molecules that are critical in the maturation of actin aggregates to functional sealing rings. L-plastin was described to be homologous with the F-actin-bundling protein fimbrin (59), and it is present in the podosomes of osteoclasts (2,60). However, its function in osteoclasts is highly unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Journal of Cell Science 118 (6) stabilized F-actin structures by displacing cofilin (Nakano et al, 2001). Whether T-plastin and cofilin compete for binding to the same site on the actin filament or might indirectly influence their binding by inducing a conformational change in the actin subunit, as supported by structural and biochemical data (Hanein et al, 1998;McGough et al, 1997), remains to be experimentally evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium insensitivity could be due to poor conservation of the N-terminal calmodulin-like calcium binding domain (McCurdy and Kim, 1998;Staiger and Hussey, 2004). Calcium insensitivity was also reported for chicken fimbrin (Bretscher, 1981) and S. pombe Fim1p (Nakano et al, 2001). By contrast, plastins from mammalian cells (Namba et al, 1992;Lin et al, 1994) and Dictyostelium (Prassler et al, 1997) have been shown to be calcium sensitive.…”
Section: Fim5 Is a Bona Fide Actin Bundling Factormentioning
confidence: 98%
“…In addition, fimbrin has been shown to localize to the cortical region of the cleavage furrow in Tetrahymena pyriformis and to the cortical actin patches and the medial ring in the fission yeast S. pombe, suggesting a possible role for fimbrin in cytokinesis Shirayama and Numata, 2003;Wu and Pollard, 2005). Fission yeast fim1+ organizes actin filaments into bundles in vitro, and loss-of-function of S. pombe fim1+ increases the sensitivity of actin filaments to latrunculin A treatment (Nakano et al, 2001), suggesting that fim1+ is involved in stabilization of actin filaments in cytokinesis. Interestingly, mutation of fimbrin in Dictyostelium does not affect growth, endocytosis, exocytosis, or chemotaxis but causes a small cell phenotype (Pikzack et al, 2005).…”
Section: Introductionmentioning
confidence: 99%